Peruntukan undang-undang wasiat wajibah di Mesir dan Selangor: kajian perbandingan - Mohd Zamro Muda; Mohd Shukri Jusoh (Penerbit Universiti Kebangsaan Malaysia, 2005)
Obligatory will is a part of inheritance provided by law to orphaned grandchildren who are blocked by certain individuals. Egypt is the first Islamic country which promulgates the law concerning obligatory will in its legal system. In Malaysia, Selangor is the only state that took similar action which is provided in the Muslim Will Enacment (Selangor) 1999. The aim of this paper is to compare the law of obligatory will in Egypt and Selangor. The methodology used in this paper is the libarary research whereby relevant materials are collected and analyzed. The result shows that there are differences and similarities between both lagislations on this subject. The difference can be seen on the eligible grandchildren of obligatory will in the Egyptian legal system is more comprehensive than the one in Selangor. Whereas the similarities can be identified on several aspects such as conditions, amount and solving approach